Synergism between a foldase and an unfoldase: reciprocal dependence between the thioredoxin-like activity of DnaJ and the polypeptide-unfolding activity of DnaK - Mattoo, Rayees U. H.; Farina Henriquez Cuendet, America; Subanna, Sujatha; Finka, Andrija; Priya, Smriti; Sharma, Sandeep K.; Goloubinoff, Pierre (Frontiers in Molecular Biosciences, 2014)
The role of bacterial Hsp40, DnaJ, is to co-chaperone the binding of misfolded or alternatively folded proteins to bacterial Hsp70, DnaK, which is an ATP-fuelled unfolding chaperone. In addition to its DnaK targeting activity, DnaJ has a weak thiol-reductase activity. In between the substrate-binding domain and the J-domain anchor to DnaK, DnaJ has a unique domain with four conserved CXXC motives that bind two Zn2+ and partly contribute to polypeptide binding. Here, we deleted in DnaJ this Zn-binding domain, which is characteristic to type I but not of type II or III J-proteins. This caused a loss of the thiol-reductase activity and strongly reduced the ability of DnaJ to mediate the ATP- and DnaK-dependent unfolding/refolding of mildly oxidized misfolded polypeptides, an inhibition that was alleviated in the presence of thioredoxin or DTT. We suggest that in addition to their general ability to target misfolded polypeptide substrates to the Hsp70/Hsp110 chaperone machinery, Type I J-proteins carry an ancillary protein dithiol-isomerase function that can synergize the unfolding action of the chaperone, in the particular case of substrates that are further stabilized by non-native disulfide bonds. Whereas the unfoldase can remain ineffective without the transient untying of disulfide bounds by the foldase, the foldase can remain ineffective without the transient ATP-fuelled unfolding of wrong local structures by the unfoldase.